Cellulose- and Saccharide-Based Orally Dispersible Thin Films Transform the Solid States and Dissolution Characteristics of Poorly Soluble Curcumin - Helmy Yusuf; Orchidea Meidy Nurintan Savitri; Nadia Natsya Al-Khalifi; Lavinia Gunawan; Brian Karno Chairul; M. Agus Syamsur Rijal; Dewi Isadiartuti; Retno Sari (Advances in Pharmacological and Pharmaceutical Sciences)
This study aimed at developing and optimizing the orally dispersible thin film (ODTF) containing a plant-derived drug—curcumin (CUR). CUR belongs to a biopharmaceutical classification system (BCS) class IV compound that requires improving its water solubility and tissue permeability preceding formulation. An ODTF was applied to produce a solid dispersion matrix for CUR to resolve such solubility and permeability problems. The film-forming polymers used in the study were cellulose-based (hydroxypropyl methylcellulose/HPMC and carboxymethylcellulose/CMC) and saccharide-based maltodextrin (MDX). Poloxamer (POL) was also employed as surfactant and solubilizer. The solvent casting technique was applied to produce the films. The ethanolic solution of CUR was mixed with an aqueous solution of POLs and then incorporated into different film-forming polymers prior to casting. The processing of the CUR with POL solution was intended to aid in the even dispersion of the drug in the polymeric matrices and enhance the wettability of the films. The physical state and properties of the films were characterized in terms of their morphology, crystallinity of the drug, and phase miscibility of the mixtures. The dissolution profile of the films was also evaluated in terms of dissolution rate and dissolution efficiency. The obtained ODTF products were smooth and flat-surfaced. Physical characterization also indicated that the CUR was homogeneously dispersed in the ODTFs and no longer existed as crystalline material as revealed by X-ray diffraction (XRD). The CUR was also not phase-separated from the films as disclosed by differential scanning calorimetry (DSC). Such dispersion was achieved through the solubilizing effect of POLs and compact polymeric film matrices that prevented the CUR from recrystallization. Furthermore, the ODTFs also improved the dissolution of CUR by 3.2-fold higher than the raw CUR. Overall, cellulose-based films had favorable physical properties compared with saccharide-based films.